Impact of the occupational health and safety management system (OHSMS) on human talent management and organizational performance in the construction sector - Navarro Claro, Genny Torcoroma; Bayona Soto, José Andrés; Arévalo Ascanio, José Gregorio (Frontiers in Built Environment, 2025)
ObjectiveThis study analyzes the impact of the Occupational Health and Safety Management System (OHSMS) on People Management (PM) and Organizational Performance (OP) in the construction sector, emphasizing its role in organizational sustainability and efficiency.MethodologyA theoretical model was validated to evaluate the direct and mediated relationships between OHSMS, PM, and OP using Structural Equation Modeling (SEM). Data were collected from 239 workers across 50 construction companies in Norte de Santander, Colombia, through structured surveys and secondary institutional sources. Exploratory data analysis, Spearman correlations, and SEM were applied, confirming the instrument’s reliability and construct validity.ResultsThe OHSMS showed a significant direct effect on OP, which was substantially enhanced when mediated by PM. Key people management practices such as planning, participation, and continuous evaluation emerged as crucial links. Moreover, PM positively influenced OP dimensions such as wellbeing, equity, system perception, and job satisfaction.ConclusionIntegrating OHSMS with strategic human resource practices is critical for optimizing organizational performance in high-risk sectors like construction. The findings offer practical guidelines for aligning safety systems with people management to foster sustainable and efficient organizations.Practical implicationsThe study recommends embedding participatory mechanisms, training, and wellbeing strategies within OHSMS implementation to improve commitment and operational outcomes. These insights can inform business policies, organizational training programs, and future sectoral interventions.